The estimation of distances between specific backbone-labeled sites in DNA using fluorescence resonance energy transfer. - Ozaki, H (1992)
A series DNA helices of twenty-four base pairs has been prepared for the study of fluorescence resonance energy transfer. Each of the DNA helices contains two phosphorothioate diesters (one in each strand) at pre-selected sites for introduction of the desired donor and acceptor fluorophores. The phosphorothioate-containing oligodeoxynucleotides have been prepared as pure Rp or Sp derivatives or as deastereomeric mixtures. Fluorescein and eosin are employed as the respective donor and acceptor fluorophores. A series of donor-acceptor pairs was generated by labeling of the appropriate phosphorothioate diester with the desired fluorophore and annealing the two complementary DNA strands (one containing the acceptor and one containing the donor fluorophore) to form the double-stranded helix. The 24-mer helices containing two covalently attached fluorophores exhibited some thermal destabilization and the extent of this destabilization was dependent upon the stereochemical orientation of the fluorophore. The Sp derivatives direct the fluorophore out, away from the the DNA helix, while the Rp derivatives direct the fluorophore toward the major groove. As expected, the Sp labeled duplexes were more stable than the corresponding Rp labeled sequences. However, all of the duplex structures formed were stable under the conditions used to measure energy transfer. Energy transfer could be observed with these complexes from the quenching of the donor fluorescence in the presence of the acceptor fluorophore. Using Förster's theories, distances separating the fluorophores could be calculated that were generally in reasonable agreement with the distances expected in an idealized B-form DNA helix. However anomalous results were obtained for one donor/acceptor pair where the expected distance was less than 20 A. Fluorescence anisotropy values determined in solutions of varying viscosity were quite high suggesting that the fluorophores did not experience complete freedom of movement when attached to the DNA helix.